Using the theory of inventive problem solving to brainstorm innovative ideas for assessing varieties of phone-cameras. (July 2015) - Wang, Chih-Hsuan
Highlights: TRIZ (the theory of inventive problem solving) is used to design phone-cameras. ARM (association rule mining) is employed to identify critical product features. CA (conjoint analysis) is conducted to evaluate varieties of design alternatives. Samsung's S4 zoom, K zoom and galaxy camera are used for benchmarking. Asus's Zenfone zoom justifies the validity of the suggested periscopic lenses. Abstract: Today, to survive in an extremely turbulent business environment, traditional products characterized by limited capabilities cannot satisfy diverse customer requirements. In particular, it is observed that the boundaries between smart phones, digital cameras, and tablets are becoming more and more blurred than before. Therefore, for attracting the ad-hoc segments, global companies began to develop hybrid pad-phones and phone-cameras. Unfortunately, some of these products are facing poor sales without incurring much market attention. In order to overcome the aforementioned difficulty, this paper presents a novel framework to reduce the gaps between producer expectation and user perception. By means of the TRIZ (the theory of inventive problem solving), a contradiction matrix is applied to handle engineering conflicts among multi-functional alternatives to seek inventive solutions. Then, ARM (association rule mining) is conducted to identify critical features that formulate customer dissatisfaction (purchase intention). Finally, CA (conjoint analysis) is employed to derive customer utilities for benchmarking varieties of design concepts. In summary, the proposed framework cannot only help product planners efficiently generate innovative ideas, but also effectively justify the validity of design concepts.